Use of our Protocol of Multimodality Tools to Aid in the Safe Microsurgical Clipping of Unruptured Anterior Circulation Aneurysms - Kannan, Satish (Asian J Neurosurg, 2019)
OBJECTIVES: The aim of this study is to analyze the effectiveness of our protocol of the use of multimodality tools, namely indocyanine green-dual image video angiography, neuroendoscope, neuromonitoring with motor-evoked potential, micro-Doppler in the microsurgical clipping of unruptured anterior circulation aneurysms, operated at our institute from January 2016 to December 2018. MATERIALS AND METHODS: We performed a retrospective analysis of all cases of unruptured anterior circulation aneurysms, operated at Fujita Health University Banbuntane-Hotokukai Hospital, Japan, from January 2016 to December 2018. We assessed outcome at immediate postoperative, at discharge, and at 3 months follow-up by defining permanent morbidity as drop in Modified Rankin Scale (MRS) by 1 at 3 months follow-up and transient morbidity as temporary deficit that improved at discharge or follow-up. Postoperative events, namely seizures, infection that did not affect/change. Preoperative MRS and discharge timing were excluded. We concluded poor outcome as MRS ≥3 and good outcome as MRS < 3 (0–2). All patients had a minimum of 3 months follow-up before outcome conclusion. RESULTS: In 2016, a total of 98 cases were operated with no mortality or permanent morbidity (i.e., change in preoperative MRS), only transient morbidity was seen in (two cases) 2.04%. In 2017, a total of 119 cases were operated with no mortality or morbidity. In 2018, a total of 130 cases were operated with no mortality or permanent morbidity, only transient morbidity 0.7%. Summarizing from January 2016 to December 2018, a total of 347 cases of anterior circulation aneurysms were operated. Mostly, in the female sex (73.3%), the most common was middle cerebral artery aneurysm (39.1%). The mean size was 5.3 mm with no mortality or permanent morbidity with only transient morbidity in 0.9%. No poor outcome (MRS ≥3) was seen in our series. CONCLUSION: In our center for most unruptured anterior circulation aneurysms, microsurgical clipping is the treatment of choice. We believe our protocol of the intra-operative usage of multimodality tools have aided in the safe microsurgical clipping and have consistently resulted in good operative outcomes. Hence, we recommend and continue to use our Fujita-Bantane Protocol in all cases of micro-surgical clipping of aneurysms to consistently achieve good operative outcomes.